The Influence of Viral Marketing and Buy Now, Pay Later Promotion on Impulsive Buying of Sneakers in E-commerce: The Mediating Role of Hedonic Motivation and Fear of Missing Out (FOMO) - Sonday, Mahendra Ramadhan; Nurbaiti, Yessy; Mustikasari, Faranita (Dinasti Publisher, 2025)
Post-pandemic economic recovery in Indonesia has posed significant challenges to the fashion industry, especially footwear. Although the sector grew by 44.02% in 2022, it sharply declined to only 2.65% by Q2 2024. This research investigates how viral marketing campaigns and Buy Now, Pay Later (BNPL) promotions influence impulsive buying behavior among e-commerce consumers, with hedonic motivation and Fear of Missing Out (FOMO) as mediating psychological mechanisms. Using a quantitative approach based on the Stimulus–Organism–Response (S–O–R) framework, data from 339 valid respondents aged 25–44 in Jabodetabek who have experience purchasing sneakers online were analyzed using PLS-SEM. The findings reveal that both viral marketing and BNPL promotions directly enhance impulsive buying tendencies. BNPL significantly strengthens hedonic motivation, which mediates its effect on impulsive purchasing. FOMO directly influences impulsive buying, but does not mediate the impact of viral marketing. However, descriptive statistics show that perceptions of BNPL and hedonic motivation remain neutral to low. These findings highlight the critical role of emotionally resonant marketing in stimulating consumer response in digital platforms.